The effect of upper- and lower-body exercise on next-day postprandial triglycerides in healthy young men - Zhong, Zhentao; Miyachi, Motohiko; Tanisawa, Kumpei (Frontiers in Physiology, 2024)
The incremental TG area under the curve (AUC) (main effect of trial, P = 0.012) was 39% and 37% higher in the control trial than in the upper-and lower-body exercise trials (P = 0.025 and P = 0.033, respectively). There were no significant differences in incremental TG AUC between the upper-and lower-body exercise trials.An acute bout of energy-matched upper-and lower-body exercises similarly lowered postprandial TG concentrations the following day in healthy young men.Trial registration number: UMIN000045449.